Associação de goma arábica e eugenol na carcinogênese colorretal, estresse oxidativo e genotoxicidade em fígado, pulmão, baço e rim de ratas submetidos ao dimethilhidrazina - Melo, Nayanna de Oliveira Ramos (2023)
The target of much research has been to search for compounds that can prevent, delay, or reverse the carcinogenesis process. Arabic gum and eugenol have antioxidant properties that have already been described in some studies, therefore, they may have therapeutic potential for neoplastic diseases. The objective of this study was to evaluate the effects of arabic gum and eugenol on dimethylhydrazine (DMH)-induced colorectal carcinogenesis in Wistar rats and their effects on the liver, spleen, kidney, and lungs. To evaluate prevention, control groups received Ia (water - 5 ml/kg body weight), IIa (10% arabic gum - 5 ml/kg body weight), IIIa (eugenol - 100 ml/kg body weight), IVa (eugenol - 100 ml/kg body weight + 10% arabic gum - 5 ml/kg body weight) and 0.5 ml of sterile 0.9% saline solution (SF) subcutaneously (SC) once a week for 20 weeks. Experimental groups received V (water - 5 ml/kg body weight), VI (10% arabic gum), VII (eugenol - 100 ml/kg body weight), VIII (eugenol - 100 ml/kg body weight + 10% arabic gum) and DMH at a dose of 20 mg/kg body weight, subcutaneously, once a week for 20 weeks. To evaluate treatment, control groups received 0.5 ml of sterile 0.9% saline solution (SF) subcutaneously (SC) once a week for 20 weeks. Subsequently, they received the test substances via gavage for 9 weeks - Ib (water - 5 ml/kg body weight), IIb (10% arabic gum - 5 ml/kg body weight), IIIb (eugenol - 100 ml/kg body weight), IVb (eugenol - 100 ml/kg body weight + 10% arabic gum - 5 ml/kg body weight). Experimental groups received DMH at a dose of 20 mg/kg body weight, subcutaneously, once a week for 20 weeks. Subsequently, they received the test substances via gavage for 9 weeks - IX (water - 5 ml/kg body weight), X (10% arabic gum), XI (eugenol - 100 ml/kg body weight), XII (eugenol - 100 ml/kg body weight + 10% arabic gum).At the end, the colon was evaluated through histopathological study with hematoxylin-eosin (HE) and study of aberrant crypts using stereoscopic microscopy to determine the number of aberrant crypts, aberrant crypt foci (ACF), and crypts per focus (multiplicity) (stained with 1% methylene blue) per colon segment (proximal, middle, and distal), in addition to the collection of colon, liver, blood, bone marrow, spleen, kidney, and lungs for the study of oxidative stress and genotoxicity. In prevention, the concomitant use of 10% arabic gum and eugenol, as described in the doses and time, showed a synergistic and effective effect in reducing the number of aberrant crypts and aberrant crypt foci in the colon segment (distal and total colon) and ACF with less than 5 crypts in the total colon. In prevention and treatment, the concomitant use of 10% arabic gum and eugenol was effective in reducing genotoxicity and oxidative stress in the colon, liver, spleen, kidney, as well as reducing lipid peroxidation in the blood and systemic genotoxicity (bone marrow) in rats subjected to DMH-induced colorectal carcinogenesis.